Influence of Mesophilic Bacteria Inoculation with Chicken Manure for Biogas Production Enhancement in Anaerobic Digestion (AD) Process - Alkarimiah, Rosnani (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The objective of this study is to investigate biogas production by anaerobic digestion using mesophilic bacteria mixed with Palm Oil Mill Effluent (POME). This project aims to determine the volume of biogas generation and volatile fatty acid (VFA) production from chicken manure via the anaerobic digestion process. Anaerobic digestion (AD) of chicken manure (CM) often faces obstacles, including high total ammonia nitrogen (TAN) concentration, inorganic soil particles, and wood chips.
Keywords: anaerobic digestion; POME; chicken manure; methane production; bacteria